2014
DOI: 10.1126/science.1251151
|View full text |Cite
|
Sign up to set email alerts
|

Fermi arcs in a doped pseudospin-1/2 Heisenberg antiferromagnet

Abstract: High-temperature superconductivity in cuprates arises from an electronic state that remains poorly understood. We report the observation of a related electronic state in a noncuprate material, strontium iridate (Sr2IrO4), in which the distinct cuprate fermiology is largely reproduced. Upon surface electron doping through in situ deposition of alkali-metal atoms, angle-resolved photoemission spectra of Sr2IrO4 display disconnected segments of zero-energy states, known as Fermi arcs, and a gap as large as 80 mil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
282
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 307 publications
(311 citation statements)
references
References 43 publications
20
282
2
Order By: Relevance
“…Above this temperature, the d-wave gap evolves into a pseudogap, in striking parallel with the cuprates 12,16 . However, because of the inherently surface sensitive nature of the technique used to dope the sample in these studies, involving in situ deposition of alkali metal atoms on the surface of undoped Sr 2 IrO 4 , it remains unclear at this point whether the dwave gap originates from superconductivity without evidence from bulk measurements.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Above this temperature, the d-wave gap evolves into a pseudogap, in striking parallel with the cuprates 12,16 . However, because of the inherently surface sensitive nature of the technique used to dope the sample in these studies, involving in situ deposition of alkali metal atoms on the surface of undoped Sr 2 IrO 4 , it remains unclear at this point whether the dwave gap originates from superconductivity without evidence from bulk measurements.…”
Section: Introductionmentioning
confidence: 89%
“…Experimentally, it has been confirmed that the canted antiferromagnetic structure of Sr 2 IrO 4 derives from a predominantly isotropic nearest-neighbor magnetic exchange coupling [8][9][10] . Thus, Sr 2 IrO 4 becomes the first non-cuprate material to realize a (iso)spin-1/2 Heisenberg antiferromagnet in a quasitwo-dimensional square lattice-a possible platform for high temperature superconductivity [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Rh substitutions, which results in effective hole doping 13 , a metallic-like state was observed, albeit with residual pseudogaps instead of well defined quasiparticles (QP) peaks 14 . Another kind of metallic state was observed by evaporating K on the surface of Sr 2 IrO 4 , which presumably dopes electrons into it 15 . In this case, well defined QP were observed, with strong momentum and temperature dependences that resemble those found in the cuprates and even possible signs of superconductivity 16,17 4 18 .…”
mentioning
confidence: 99%
“…In the case of surface doped Sr 2 IrO 4 (which yields electron doping, like La), a good metallic state, with well defined QP and circular FS, seems to be realized 15 . Interestingly, the position of the J=3/2 band in this study is back to its original position near -0.5eV (see Fig.…”
mentioning
confidence: 99%